Practical ship design - Watson, David G. M. (Elsevier ocean engineering book series ;)
The ever-growing demand for commercial activities at sea has meant that ships are rapidly developing and that the rules governing their construction and operation are changing. Practical Ship Design records these changes, their outcomes and the reasoning behind them. It deals with every aspect of ship design and handles a wide range of both merchant ships and naval ships with authority. It provides coverage of cargo ships and passenger ships, tugs, dredgers and other service craft. It also includes concept design, detail design, structural design, hydrodynamics design, the effect of regulations, the preparation of specifications and matters of costs and economics. Drawing on the author's extensive practical experience, Practical Ship Design is likely to interest everybody involved in the design, construction, repair and operation of ships. Students and the most experienced professionals will all benefit from the book's vast store of design data and its conclusions and recommendations.